Novel FOXL2 variants in two Chinese families with blepharophimosis, ptosis, and epicanthus inversus syndrome - Zhao, Mingyu; Meng, Xiaolu; Wang, Jiaqi; Wang, Tailing (Frontiers in Genetics, 2024)
Background: Blepharophimosis, ptosis, and epicanthus inversus syndrome (BPES) is a rare inherited disorder. This study was aimed to identify and functionally validate FOXL2 variants in two Chinese families with BPES.Methods: The proband and his family members were subjected to whole-exome sequencing to identify disease-associated variants. Several bioinformatic tools were used to computationally predict altered proteins. In vitro functional assays were conducted by transfecting wild-type and mutant FOXL2 cDNAs into HEK-293 cells, followed by subcellular localization assays, luciferase reporter gene assays, and quantitative real-time polymerase chain reaction.Results: The clinical features of BPES, including small palpebral fissures, ptosis, telecanthus, and epicanthus inversus, were present in all affected patients. Two novel mutations were detected, c.292T>A and c.383G>T. Whole-exome sequencing analysis and prediction software suggested that these mutations were pathogenic. Functional studies showed that these two point mutations decreased FOXL2 protein expression, resulting in subcellular mislocalization and aberrant transcriptional activity of the steroidogenic acute regulatory protein gene promoter. Conclusion: Our results add to the current understanding of known FOXL2 variants in, and our in vitro experiments provide reference data and insights into the etiology of BPES. Further studies are needed to identify the possible mechanisms underlying the action of this mutation on the development of BPES.